What determines the neural response to snakes in the infant brain? A systematic comparison of color and grayscale stimuli - Bertels, Julie; de Heering, Adelaïde; Bourguignon, Mathieu; Cleeremans, Axel; Destrebecqz, Arnaud (Frontiers in Psychology, 2023)
Snakes and primates have coexisted for thousands of years. Given that snakes are the first of the major primate predators (Isbell, 2009), natural selection may have favored primates whose snake detection abilities allowed for better defensive behavior. Aligning with this idea, we recently provided evidence for an inborn mechanism anchored in the human brain that promptly detects snakes, based on their characteristic visual features (Bertels et al., 2020). What are the critical visual features driving human neural responses to snakes is an unresolved issue. While their prototypical curvilinear coiled shape seems of major importance (Bertels et al., 2020; Lobue & Deloache, 2011), it remains possible that the brain responds to a blend of other features. Coloration, in particular, might be of major importance, as it has been shown to act as a powerful aposematic signal (Stevens & Ruxton, 2012). Here, we specifically examine whether color impacts snake-specific responses in the naive, immature infant brain. For this purpose, we recorded the brain activity of 6- to 11-month-old infants using EEG, while they watched sequences of color or grayscale animal pictures flickering at 6Hz. We showed that glancing at colored and grayscale snakes generates specific neural responses in the occipital region. Color did not exert a major influence on the infant brain response but strongly increased the attention devoted to the sequences. Remarkably, age predicted the strength of the snake-specific response. These results highlight that the expression of the brain-anchored reaction to coiled snakes bears on the refinement of the visual system.